FRI0154 The tolerability of vaccination against pneumococcus in children with juvenile idiopathic arthritis. (15th June 2017) - Soloshenko, M; Alexeeva, E; Bzarova, T; Valieva, S; Denisova, R; Lomakina, O; Isaeva, K; Kashchenko, E; Karaseva, A
Abstract : Background: Children with chronic rheumatic diseases, including juvenile idiopathic artritis, are at high risk of bacterial and viral infections. The risk of complications and severity of infectious diseases are increased in immunosuppressive therapy due to given the long-term use. Objectives: To evaluate the safety and tolerability of vaccination against pneumococcus in children with juvenile idiopathic arthritis. Methods: The analysis included 39 patients with juvenile idiopathic arthritis who were in remission. Patients were divided into two groups, depending on the type of immunosuppressive therapy. Group 1 (n=24) consisted of patients receiving etanercept, mean age 5, 4±2, 5, observed 48 patient-years; Group 2 (n=15), patients who received methotrexate mean age 6, 8±3, 2, observed 30 patient-years. All patients had been vaccinated by 13-valent pneumococcal polysaccharide conjugate vaccine (13PPV). Recorded the incidence of infection diseases (such as pneumonia, tonsillitis, otitis media, etc.) in the 12 months prior to vaccination and 12 months after vaccination. All patients monitored the development of adverse events against the background of vaccination. Results: The study showed a decrease in the incidence ofinfection diseases after vaccination in the first group from 5, 4±1, 66 to 1, 7±0, 77, in second group from 4, 4±1, 05 to 1, 6±0 73, (p<0.05). Adverse events related to vaccination are presented in the table. Results of the study showed no relapse of the underlying disease following immunization. Adverse events related to vaccination are presented in the table. Conclusions: The results showed a good tolerability of the vaccine, no relapse of the underlying disease following immunization, as well as a statistically significant (p<0.05) reduction in the incidence following immunization. Disclosure of Interest: M. Soloshenko: None declared, E. Alexeeva Grant/research support from: Roche, Abbott, Pfizer, Bristol-Myers Squibb, Centocor, Novartis., Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Bristol-Myers Squibb, Medac, Novartis, Pfizer, T. Bzarova Grant/research support from: Roche, Pfizer, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Pfizer, S. Valieva Grant/research support from: Roche, Bristol-Myers Squibb, Speakers bureau: Roche, Merck Sharp & Dohme, Bristol-Myers Squibb, Medac, Novartis, R. Denisova Grant/research support from: Roche, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp & Dohme, Abbott, Medac, O. Lomakina: None declared, K. Isaeva: None declared, E. Kashchenko Grant/research support from: Novartis, A. Karaseva: None declared